HUBUNGAN PENGETAHUAN LINGKUNGAN DENGAN SIKAP MASYARAKAT TERHADAP PELESTARIAN LINGKUNGAN DI KAWASAN LINDUNG NGARAI SIANOK BUKITTINGGI - Desriana Desriana (LPPM Universitas Muhammadiyah Sumatera Barat, 2020)
The attitude of the community towards the environment is influenced by many factors, including the level of income and environmental knowledge. The level of income can be related to various characteristics such as achievement motivation, dropping out of school, academic achievement, and how a person can interact with his environment. Communities with low socioeconomic conditions with low incomes have low participation rates and attitudes, do not want to know, and do not care about environmental improvement both regarding regulations and garbage, even though they know that an unhealthy and irregular environment can lead to various kinds problem. This research uses quantitative methods with the type of research is descriptive analytic. The population of this study is the entire community who live in a protected area along the outskirts of the Siaonok Bukittinggi Gorge which is 100 m from the edge of the canyon, totaling 1,049 families (KK). The sampling technique uses a sampling area based on the number of HHs found in each village. Data collection techniques were carried out using the help of a questionnaire. Data analysis techniques using descriptive statistical techniques and inferential statistics. From the analysis of data there is a significant relationship between the level of environmental knowledge with community attitudes in environmental conservation with a relation coefficient of 0.602 and an observer probability value of 0,000. For this reason, it is recommended that (1) the government enforce the law regarding the prohibition of living above the Sianok canyon at a distance of less than 10 m and involve the community actively in the process of preservation in the process of environmental preservation by managing protected areas as community-based tourism areas. (2) the community is advised not to live above the canyon less than 100 m by renting or contracting land and houses in areas far from the Sianok canyon. Keywords: Knowledge, Attitude, Conservation, Environment